Primary health care nurses: attitudes towards the person with mental disorder - Maria do Perpétuo Socorro de Sousa Nóbrega; Carla Sílvia Neves da Nova Fernandes; Sonia Regina Zerbetto; Francisco Miguel Correia Sampaio; José Carlos Carvalho; Suellen Cristina da Silva Chaves (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To identify the attitudes of nurses working in Primary Health Care towards the person with mental disorder and the variables related to health care provided. Methodology Descriptive, correlational study with 250 nurses from 69 Basic Health Units in the city of São Paulo. Data collection took place between April and August 2019 using the "Opinions about Mental Illness" scale. The data were analyzed using the KrusKal-Wallis test, with a 95% confidence level and statistical significance of p <0.05. Results The global mean of the scale was 197, which shows negative attitudes especially in the dimensions of Authoritarianism (44.6), Social Restriction (42.0), and positive in the dimension of Benevolence (51.7). Conclusion Nurses tend to have a stigmatizing attitudinal profile. It is necessary formative and permanent intervention so that it is possible to reduce stigma and improve community-based care recommended in the guidelines of the Psychosocial Care Network.